2015
DOI: 10.1186/s12960-015-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the data revolution: identifying minimum health information competencies among the health workforce

Abstract: BackgroundHealth information is required for a variety of purposes at all levels of a health system, and a workforce skilled in collecting, analysing, presenting, and disseminating such information is essential to fulfil these demands. While it is established that low- and middle-income countries (LMICs) are facing shortages in human resources for health (HRH), there has been little systematic attention focussed on non-clinical competencies. In response, we developed a framework that defines the minimum health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Currently, NI are suggested to be core competencies instead of an isolated set of skills in nursing (Abdrbo 2015;Kleib and Nagle 2018;Sipes et al 2017). Informatics competency requirements are set for different roles and all levels of nurses (nurse administrators, nurse researchers, nurse teachers and practicing nurses) (Collins et al 2017;Egbert et al 2018;Grobe 1989;Kannry et al 2016;Skiba 2016;Strudwick et al 2019) and across different levels in health systems, ranging from service providers to national-level strategic decision makers (Whittaker et al 2015). However, a systematic and formal approach to the implementation of NI in nursing education is still lacking in some countries (Cummings et al 2015;Egbert et al 2018), and research has shown that graduate nurses are inadequately prepared in NI when entering practice (Shin et al 2018) and that more NI training is needed at postgraduate levels in nursing (Choi et al 2013;Kupferschmid et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, NI are suggested to be core competencies instead of an isolated set of skills in nursing (Abdrbo 2015;Kleib and Nagle 2018;Sipes et al 2017). Informatics competency requirements are set for different roles and all levels of nurses (nurse administrators, nurse researchers, nurse teachers and practicing nurses) (Collins et al 2017;Egbert et al 2018;Grobe 1989;Kannry et al 2016;Skiba 2016;Strudwick et al 2019) and across different levels in health systems, ranging from service providers to national-level strategic decision makers (Whittaker et al 2015). However, a systematic and formal approach to the implementation of NI in nursing education is still lacking in some countries (Cummings et al 2015;Egbert et al 2018), and research has shown that graduate nurses are inadequately prepared in NI when entering practice (Shin et al 2018) and that more NI training is needed at postgraduate levels in nursing (Choi et al 2013;Kupferschmid et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Out of all the 27 studies, five studies were carried out in different areas of Victoria [86,88,92,98,99], five in New South Wales [83,89,91,101,103], five in Queensland [76,93,95,100,104], three studies in Western Australia [81,85,90], two studies in South Australia and Australia Capital Territory respectively [77,78,80,94], and one study each in Tasmania and the Northern Territory, and one study recruited participants from all of the states and territories except Tasmania [70,72,73]. One study recruited participants from across Australia [79], and one study was carried out among Indigenous Australians [87].…”
Section: Resultsmentioning
confidence: 99%
“…The present review also brought forth the time sequence of all the included studies related with health literacy. Three studies were published before the years 2010 [77,79,87] and 25 studies were published between 2010 and 2018 [76,78,80,81,83,85,86,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104]. The spatial and temporal sequence demonstrates that health literacy research is Australia is widespread and most studies have been published since 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Paper-based systems are human resource and time intensive and are often plagued by inaccurate reporting processes leading to out-of-date and irrelevant data 35. An effective EMR is an essential component of a robust and efficient modern healthcare system 3 , 6 , 7…”
Section: Introductionmentioning
confidence: 99%